THE IDDAH PERIOD IN ISLAMIC JURISPRUDENCE AND STATUTORY LAW IN INDONESIA AND SINGAPORE - Siti Nurheliza; Sukiati Sukiati; Iwan Iwan (Hukum tata Negara/Siyasah, 2026)
Iddah is a mandatory waiting time that Muslim women must observe after the dissolution of marriage, whether by divorce or the death of a spouse, prior to being allowed to remarry. This research seeks to examine the notion of iddah through the lens of Islamic jurisprudence (fiqh) and to contrast its regulation under the legal frameworks of Indonesia and Singapore. This study utilizes a normative legal research methodology, including statutory, conceptual, and comparative methods via the examination of Islamic legal sources, statutory regulations, and diverse literature pertaining to Islamic family law. The results demonstrate that the idea of iddah in classical fiqh has a robust normative basis derived from the Qur’an, Hadith, and academic ijtihad, with the objectives of safeguarding lineage, protecting women's rights, and sustaining familial order. Indonesia and Singapore both use classical fiqh principles, namely the Shafi’i school, as the normative foundation for controlling iddah; nevertheless, they diverge in their institutional frameworks, implementation methods, and the incorporation of Islamic law into their legal systems. In Indonesia, the regulation of iddah is integrated into the national legal system through the Compilation of Islamic Law and the Religious Court system, while in Singapore it is implemented through the Administration of Muslim Law Act (AMLA) and the Syariah Court within a dual legal system framework. This study demonstrates that the transformation of fiqh into positive law does not alter the fundamental substance of iddah but rather affects its implementation mechanisms and institutional legal structures in each country.Keyword: Iddah, Islamic jurisprudence, positive law, Indonesia, Singapore.